"And they told two friends…and so on": RJ Reynolds' viral marketing of Eclipse and its potential to mislead the public. Issue 4 (10th March 2008) - Anderson, S J; Ling, P M
Abstract : Objective: To explore viral marketing strategies for Eclipse cigarettes used by the RJ Reynolds Company (Winston-Salem, North Carolina, USA). Methods: Analysis of previously secret tobacco industry documents and multimedia materials. Results: The failure of RJ Reynolds' (RJR) 1988 "smokeless" cigarette, Premier, was in part due to widespread bad word of mouth about the product's flavour, quality and difficulty of use. In 1994 RJR introduced an updated version of Premier, the ostensibly "reduced risk" Eclipse cigarette. RJR developed viral marketing channels to promote Eclipse using (1) exploratory interviews to motivate consumers to spread the word about Eclipse prior to market release, (2) promotional videos featuring positive feedback from test group participants to portray majority consensus among triers, (3) "Tupperware"-like parties for Eclipse where participants received samples to pass around in their social circles and (4) the Eclipse website's bulletin board as a forum for potential users to discuss the brand in their own words. These strategies targeted the brand's likeliest adopters, recruited informal and credible representatives of the product unaffiliated with RJR, and controlled the information spread about the product. Conclusions: Viral marketing techniques may be particularly useful to promote new tobacco products such as Eclipse that have limited appeal and need a highly motivated audience of early adopters and acceptors. Such techniques help evade the mass rejection that could follow mass promotion, circumvent marketing restrictions, and allow tobacco companies to benefit from health claims made by consumers. Cigarette manufacturers must be held accountable for perceived health benefits encouraged by all promotional activities including viral marketing.